2013
DOI: 10.1590/s1516-89132013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Estrus synchronization and Fixed Time Artificial Insemination (FTAI) in dairy buffaloes during seasonal anestrus

Abstract: The aim of this work was to study estrus synchronization and fixed time artificial insemination (FTAI) G1 and G2 were 20 and 41% (p<0.05) and the ovulation rates were 16.6 and 37%, respectively (p<0.05). The dominant follicle (DF) diameter on D16 was 7.9 mm in G1 and 8.9 mm in G2 (p>0.05). Thirty-five percent of the animals in G1 and 54.1% in G2 showed a diameter DF greater than 8.0 mm on D16 (p>0.05). Thus, it could be concluded that the protocols synchronized the estrus, leading the concentration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The general conception rate (CS+FS) obtained from present study the transitional period to the physiological reproductive season was 41.5% and there was no significant difference between the years (P>0.05). Similar values, 43.1 (Porto-Filho et al, 2004) and 37.0 (Frares et al, 2013) have been reported in studies carried out during the unfavorable reproductive period. In all three studies, the eCG dosage used was 400 IU.…”
Section: Discussionsupporting
confidence: 88%
“…The general conception rate (CS+FS) obtained from present study the transitional period to the physiological reproductive season was 41.5% and there was no significant difference between the years (P>0.05). Similar values, 43.1 (Porto-Filho et al, 2004) and 37.0 (Frares et al, 2013) have been reported in studies carried out during the unfavorable reproductive period. In all three studies, the eCG dosage used was 400 IU.…”
Section: Discussionsupporting
confidence: 88%
“…Various animal husbandry systems are currently used in most buffalo breeding countries, such as India ( 1 ), Brazil ( 2 ), Italy ( 3 ), and China ( 4 , 5 ), within smaller or larger farms. As the number of local buffaloes in Romania is constantly decreasing, the application of current reproductive biotechnologies in these breeds remains limited ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%